Reproductive performance of Korean native cattle (Hanwoo) focusing on calving interval and pa - Jaesung Cho; Changhee Do; Inchul Choi (The Korean Society of Animal Reproduction and Biotechnology, 2016)
The Korean native cattle, Hanwoo, is the most popular breed of beef cattle in Korea. However, the reproductive performance data are limited although reproduction is one of the most economically and biologically important in beef production. Therefore, this study was undertaken to investigate reproductive performance parameters including calving interval, parity for life time production. Data collected from 206,827 calvings were analyzed. There were no significant differences in calving interval and gestation days as parity increased from 2nd and 13rd parity cow, from spring to winter. However, we found a dramatic increase in calving interval after year 2000. About 1 month were increased per year ( y = 30.578x + 344.45 R2 = 0.9157). Interestingly, we observed that parities for life time can be affected by birth weight. Calves with 23 kg at birth showed highest parities, 3.4±2.0 times. In summary, this study provides valuable data on reproductive performance of Hanwoo and the data presented here can be used as a standard target for optimising and enhancing reproductive performance.